Clinical and Microbiological Evaluation of Travel‐Associated Respiratory Tract Infections in Travelers Returning From Countries Affected by Pandemic A(H1N1) 2009 Influenza - Jauréguiberry, Stéphane; Boutolleau, David; Grandsire, Eric; Kofman, Tomek; Deback, Claire; AÏt‐Arkoub, ZaÏna; Bricaire, François; Agut, Henri; Caumes, Eric (Journal of travel medicine, 2012)
Background Although acute respiratory tract infections (RTI) have been recognized as a significant cause of illness in returning travelers, few studies have specifically evaluated the etiologies of RTI in this population. Methods This prospective investigation evaluated travelers returning from countries with endemic influenza A(H1N1) 2009, and who were seen in our department at the onset of the outbreak (April–July 2009). Patients were included if they presented with signs of RTI that occurred during travel or less than 7 days after return from overseas travel. Patients were evaluated for microbial agents with RespiFinder plus assay, and throat culture according to clinical presentation. Results A total of 113 travelers (M/F ratio 1.2:1; mean age 39 y) were included. They were mainly tourists (n = 50; 44.2%) mostly returning from North America (n = 65; 58%) and Mexico (n = 21; 18.5%). The median duration of travel was 23 days (range 2–540 d). The median lag time between return and onset of illness was 0.2 days (range 10 d prior to 7 d after). The main clinical presentation of RTI was influenza‐like illness (n = 76; 67.3%). Among the 99 microbiologically evaluated patients, a pathogen was found by polymerase chain reaction (PCR) or throat culture in 65 patients (65.6%). The main etiological agents were influenza A(H1N1) 2009 (18%), influenza viruses (14%), and rhinovirus (20%). A univariate analysis was unable to show variables associated with influenza A(H1N1) 2009, whereas rhinorrhea was associated with viruses other than influenza (p = 0.04). Conclusion Despite the A(H1N1) 2009 influenza pandemic, rhinovirus and other influenza viruses were also frequent causes of RTI in overseas travelers. Real‐time reverse transcription‐PCR and nasopharyngeal swab cultures are useful diagnostic tools for evaluating travelers with RTI.